Tanya dr. R. Langga tentang cuaca / Claire Llewellyn; Penerjemah, Novi Vidya Sartika; Editor, Shelomi Angeli dan Winny Rachmayanti - LLEWELLYN, Claire; NOVI Vidya Sartika; SHELOMI Angeli; WINNY Rachmayanti (Erlangga, 2013)
32 hlm. : Ilus. ; 25 cm.